ANALISIS DAN PERANCANGAN SISTEM BERBASIS WEBSITE STASIUN METEOROLOGI EL TARI KUPANG - Maria P C Seran; Yelly Y Nabuasa; Meiton Boru (J-ICON : Jurnal Komputer dan Informatika, 2016)
Meteorological Station El Tari Kupang (El Tari Kupang Stamet) has a fundamental duty to implement functionsin the field of Meteorology BMKG in particular to support the safety of air transportation and provide public information such as weather forecasts of NTT province, weather forecasts cruise along the waters of the sea wave heightin NTT and early warning of bad weather. Problem that often encountered is the dissemination of information that is still less effective and efficient. To overcome these problems,a website is designed as a media to deliver information quickly and can be accessed anywhere. In this research,the website is designed and manufactured, where the process begins with the analysis of needs and roles of the users, and then create the design to realize those needs. The next process is to implement it by making an appropriate website design and the final process of this research is testing the system. This website is built using PHP and Mysql languange programes. The output soft his website are in the form of profile information, news, galleries, downloads, employee data, image data, maritime weather information, maritime weather maps, provinces weather information, early warning of bad weather, airline data, guest book and flight information document.